Transformation from Conventional Economics to Sharia Economics: A Conceptual Analysis - Ahmad Abdul Gani (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The global economic landscape has witnessed a significant shift towards the principles of Sharia economics, driven by ethical considerations and the pursuit of sustainable financial practices. This paper provides a conceptual analysis of the transformation from conventional economic systems to Sharia-compliant economic frameworks. It delves into the foundational principles of both economic paradigms, highlighting the inherent differences and the reasons behind the growing appeal of Sharia economics. The paper also discusses the challenges faced during this transformation and the potential benefits that can be reaped by nations and institutions that successfully integrate Sharia principles into their economic structures. Through a comprehensive review of existing literature and case studies, this paper aims to offer insights into the future trajectory of global economics influenced by Sharia principles.